2018
DOI: 10.1186/s12938-018-0613-2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive filtering of physiological noises in fNIRS data

Abstract: The study presents a recursive least-squares estimation method with an exponential forgetting factor for noise removal in functional near-infrared spectroscopy data and extraction of hemodynamic responses (HRs) from the measured data. The HR is modeled as a linear regression form in which the expected HR, the first and second derivatives of the expected HR, a short-separation measurement data, three physiological noises, and the baseline drift are included as components in the regression vector. The proposed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 86 publications
0
30
0
Order By: Relevance
“…Funane et al (2015) showed that hemoglobin signals obtained with short distances channels (∼1.5 cm) were better correlated with laser-doppler flowmetry measures of scalp blood flow than signals obtained from standard emitter/detector distances (∼3 cm) targeted to measurements of blood flow in adult cortex. Additionally, Nguyen et al (2018) showed there was no correlation (r < 0.38) of short separation channels to other physiological noises present in long range separation channels. Thus, the inclusion of short separation channels as a regressor in fNIRS analyses can reduce signal interference from scalp blood flow.…”
Section: Reducing Physiologic Sources Of Interference In Fnirsmentioning
confidence: 87%
See 2 more Smart Citations
“…Funane et al (2015) showed that hemoglobin signals obtained with short distances channels (∼1.5 cm) were better correlated with laser-doppler flowmetry measures of scalp blood flow than signals obtained from standard emitter/detector distances (∼3 cm) targeted to measurements of blood flow in adult cortex. Additionally, Nguyen et al (2018) showed there was no correlation (r < 0.38) of short separation channels to other physiological noises present in long range separation channels. Thus, the inclusion of short separation channels as a regressor in fNIRS analyses can reduce signal interference from scalp blood flow.…”
Section: Reducing Physiologic Sources Of Interference In Fnirsmentioning
confidence: 87%
“…Nguyen et al (2018) applied this principle to reduce the amount of physiological noise present in fNIRS during a finger tapping task through the linear combination of the expected hemodynamic responses to the prescribed stimuli, short separation channel signals to detect extra-cortical noise, Fourier approximations of physiological noise (heart rate, respiratory, and blood pressure fluctuations), and baseline drift. Unknown model coefficients were estimated using a recursive least-square estimator to produce an adaptive filter that was able to reduce on average 77% of noise in oxyhemoglobin and 99% of noise in deoxyhemoglobin (Nguyen et al, 2018). Some limitations of this type of filtering include parameter tuning, the need to define noise distributions, and biased estimations if the filter is not closed loop (Abdelnour and Huppert, 2009).…”
Section: Reducing Physiologic Sources Of Interference In Fnirsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified Beer-Lambert law was utilized to convert the optical densities to HbO and HbR (Sassaroli and Fantini, 2004). The converted signals passed 4th-order Butterworth low-and high-pass filters (i.e., cutoff frequencies: 0.001 and 0.1 Hz, respectively) to remove physiological noise, i.e., cardiac noise−1 Hz, respiration−0.25 Hz, and Mayer signal−0.1 Hz (Naseer et al, 2016;Khan and Hong, 2017;Nguyen et al, 2018). In accordance with our previously published evaluation results (Yang et al, 2019) and the relevant literature (Hoshi, 2007), it was observed that HbO is more sensitive and dependable than HbR.…”
Section: Fnirs Data Pre-processingmentioning
confidence: 99%
“…where i represents the channel number; y is the measured HbO/ HbR; u is the desired hemodynamic response function (dHRF); w is the physiological noise; ε is the zero-mean Gaussian noise; a n , b m , c p , and c o are unknown coefficients that are recursively estimated; and n o , m o , and p o are the orders of the system, input, and exogenous signals, respectively. For fNIRS, the exogenous signal w consists of specifically three sinusoidal signals representing cardiac, Mayer, and respiration related physiological noises (Abdelnour and Huppert, 2009;Nguyen H.-D. et al, 2018). Also, the exogenous signals can be dropped out in the estimation process (i.e., p o = 0) if the prediction/tracking of the measured signal is focused.…”
Section: Brain Activity Model and Kernel Recursive Least Squarementioning
confidence: 99%